Quality evaluation of bee pollens by chromatographic fingerprint and simultaneous determination of its major bioactive components. (December 2019) - Duan, Hong; Dong, Zeng; Li, Han; Li, Wan-rong; Shi, Shu-xiang; Wang, Qing; Cao, Wen-gen; Fang, Xue-mei; Fang, Ai-dong; Zhai, Ke-feng
Abstract: Bee pollens constitute a large number of flavonoids and thus possess great medicinal value. However different varieties of bee pollen flavonoids vary with different species and their content also differ greatly in different region. Herein, the aim of present research is to establish a method based on high performance liquid chromatography (HPLC) for quantitative analysis of flavonoids compounds and chemical fingerprint analysis of bee pollen. Five batches of rape bee pollen collected from different region of China and particularly six bee pollen species obtained in Anhui were used to establish the fingerprint. The feasibility and advantages of the used HPLC fingerprint were verified for its similarity evaluation by systematically comparing chromatograms with professional analytical software. The similarities of liquid chromatography fingerprints for five batches of rape bee pollen were more than 0.994 while six batches of different species of bee pollen were lower than 0.810. In quantitative analysis, the six compounds showed good regression (R ≥ 0.9964) within the test ranges, and all the values for the RSD were lower than 2%. The developed HPLC fingerprint method was found simple, reliable, and it was validated for the quality control and identification of bee pollen. Additionally, simultaneous quantification of six flavonoids ingredients in the bee pollen samples was conducted to reveal the variation in their content. The results indicated that the HPLC fingerprint, as a characteristic distinguishing method combining similarity evaluation and quantification analysis, can be successfully used to assess the quality and also to identify the authenticity of bee pollen. Highlights: The HPLC method was developed for simultaneous quantitative analysis of six flavonoids compounds in rape bee pollen. Chemical fingerprint analysis of bee pollen was conducted to reveal flavonoids differences in five different habitats. Chemical fingerprint analysis of bee pollen was conducted to reveal flavonoids differences in five different varieties. The developed HPLC fingerprint was simple, reliable, and validated for the quality control and identification of bee pollen.